Process! : how discipline and consistency will set you and your business free - Paton, Mike; González, Lisa (BenBella Books, Inc., 2022)
"This deep-dive into the revolutionary EOS method to strengthen a company's process component will help leaders at all companies-from early stage startups to established corporations-run better businesses and live better lives"--